COMPROMISED UTERINE HEALTH DURING POSTPARTUM PERIOD IN CROSSBRED CATTLE FOLLOWING RETENTION OF FETAL MEMBRANES - SHWETHA, K S; CHANDRASHEKHARA MURTHY, V; KRISHNASWAMY, A; RAMACHANDRA, S G; BYREGOWDA, S M; SURYANARAYANA, T (The Indian Journal of Animal Reproduction, 2016)
The postpartum uterine health was determined based upon endometrial cytology (% neutrophil, threshold fixed as 18% on day 20 postpartum and
Keywords: Cattle; Endometrial cytology; PMN cells; RFM; Total bacterial count